Improved Crystallization of Lead Halide Perovskite in Two‐Step Growth Method by Polymer‐Assisted "Slow‐Release Effect". Issue 4 (28th February 2023) - Lin, Siyuan; Wu, Shuyue; Guo, De'en; Huang, Han; Zhou, Xuefan; Zhang, Dou; Zhou, Kechao; Zhang, Wenhao; Hu, Yue; Gao, Yongli; Zhou, Conghua
Abstract: Fast reaction between organic salt and lead iodide always leads to small perovskite crystallites and concentrated defects. Here, polyacrylic acid is blended with organic salt, so as to regulate the crystallization in a two‐step growth method. It is observed that addition of polyacrylic acid retards aggregation and crystallization behavior of the organic salt, and slows down the reaction rate between organic salt and PbI2, by which "slow‐release effect" is defined. Such effect improves crystallization of perovskite. X‐ray diffraction study shows that, after addition of 2 mm polyacrylic acid, average crystallite size of perovskite increases from ≈40 to ≈90 nm, meanwhile, grain size increases. Thermal admittance spectroscopy study shows that trap density is reduced by nearly one order (especially for deep energy levels). Due to the improved crystallization and reduced trap density, charge recombination is obviously reduced, while lifetime of charge carriers in perovskite film and devices are prolonged, according to time‐resolved photoluminescence and transient photo‐voltage decay curve tests, respectively. Accordingly, power conversion efficiency of the device is promoted from 19.96 (±0.41)% to 21.84 (±0.25)% (with a champion efficiency of 22.31%), and further elevated to 24.19% after surface modification by octylammonium iodide. Abstract : Polyacrylic acid (PAA) retards aggregation and crystallization behavior of the organic salt, and slows down the reaction rate between organic salt and PbI2, by which "slow‐release effect" is defined. Such effect improves crystallization and reduces trap density, and helps to obtain a power conversion efficiency from 19.96 (±0.41)% to 21.84 (±0.25)%, and further elevated to 24.19% after surface modification.